Utilization of health belief model in comprehending diarrheal disease dynamics: a case of cryptosporidiosis in Uganda - Clovice Kankya; Justine Okello; Rogers Wambi; Lesley Rose Ninsiima; Methodius Tubihemukama; Christine Tricia Kulabako; Richard Asaba; James Natweta Baguma; Musso Munyeme; James Muleme (BMC, 2022)
Abstract Background Diarrheal diseases contribute greatly to the reported global childhood mortality and morbidity with related social, economic consequences. This study was conducted to analyze the utilization of the Health Belief Model (HBM) theory to comprehend diarrheal disease dynamics in Uganda. Methods Our study utilized a qualitative cross-sectional design among adult livestock farmers in selected farming communities. A total of 80 individuals were recruited and interviewed through Focus Discussion Groups (FDGs) (n = 6) and Key Informant Interviews (KIIs) (n = 8) to evaluate diarrheal disease dynamics. The scope of dynamics included but not limited to exposure risks, knowledge, and attitudes. Our results were presented using the five (5) constructs of the HBM. Results Perceived susceptibility; communities believed that both humans and their animals are at high risk of different kinds of diarrheal infections. The farmers believed that majority of these diarrhea infections are hard to treat especially among animals. Perceived severity; farmers believed that diarrheal diseases are characterized by loss of weight, fever, emaciation, dry eyes, severe prolonged diarrhea and sudden death. Perceived barriers; limited knowledge and misconceptions about the diarrheal infections were great inhibitors to successful disease prevention and control. Self-efficacy; farmers had fear of laxity that interventions being suggested and put in place to curb diarrheal diseases such as cryptosporidiosis would wither away with time thus endemicity of the problem in the community. Modifying factors and cues to action; most of the farmers treat animals by themselves based on; probability, traditional knowledge and previous experience. Conclusion Sustained public health interventional activities should therefore be undertaken by both human and animal health sectors with maximum community involvement. Communities suggested the need to increase preventive measures and promote household hygiene efforts to always wash hands with soap and running water in order to reduce the burden of diarrhea diseases such as cryptosporidiosis.